Where do the sick go? Health insurance and employment in small and large firms - Kanika Kapur; José J. Escarce; M. Susan Marquis; Kosali I. Simon (University College Dublin, UCD School of Economics, 2006)
Small firms that offer health insurance to their employees may face variable premiums if the firm hires an employee with high-expected health costs. To avoid expensive premium variability, a small firm may attempt to maintain a workforce with low-expected health costs. In addition, workers with high-expected health costs may prefer employment in larger firms with health insurance rather than in smaller firms. This results in employment distortions. We examine the magnitude of these employment distortions in hiring, employment, and separations, using the Medical Expenditure Panel Survey from 1996 to 2001. Furthermore, we examine the effect of state small group health insurance reforms that restrict insurers' ability to deny coverage and restrict premium variability on employment distortions in small firms relative to large firms. We find that workers with high-expected health cost are less likely to be new hires in small firms that offer health insurance, and are less likely to be employed in insured small firms. However, we find no evidence that state small group health insurance reforms have reduced the extent of these distortions. Estimating the magnitude of employment distortions in insured small firms is essential in refining reforms to the small group health insurance market.
hdl:10197/952
Keywords: J21; J63; I10; I18; 330